SARS-CoV-2 ORF3a drives dynamic dense body formation for optimal viral infectivity - Stella Hartmann; Lisa Radochonski; Chengjin Ye; Luis Martinez-Sobrido; Jueqi Chen (Nature Communications)
Abstract SARS-CoV-2 hijacks multiple organelles for virion assembly, of which the mechanisms have not been fully understood. Here, we identified a SARS-CoV-2-driven membrane structure named the 3a dense body (3DB). 3DBs are unusual electron-dense and dynamic structures driven by the accessory protein ORF3a via remodeling a specific subset of the trans-Golgi network (TGN) and early endosomal membrane. 3DB formation is conserved in related bat and pangolin coronaviruses but was lost during the evolution to SARS-CoV. During SARS-CoV-2 infection, 3DB recruits the viral structural proteins spike (S) and membrane (M) and undergoes dynamic fusion/fission to maintain the optimal unprocessed-to-processed ratio of S on assembled virions. Disruption of 3DB formation resulted in virions assembled with an abnormal S processing rate, leading to a dramatic reduction in viral entry efficiency. Our study uncovers the crucial role of 3DB in maintaining maximal SARS-CoV-2 infectivity and highlights its potential as a target for COVID-19 prophylactics and therapeutics.